1998
DOI: 10.1007/s004649900867
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomy for benign colorectal disease is associated with a significant reduction in disability as compared with laparotomy

Abstract: Laparoscopic colectomy for benign colorectal diseases was associated with significantly less disability than was laparotomy in terms of length of hospitalization as well as return to baseline partial and full activity and employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 19 publications
1
58
1
3
Order By: Relevance
“…1 As laparoscopic surgery became more popular, studies demonstrated the safety and efficacy of laparoscopic colorectal surgery with the advantages of decreased pain, better cosmesis, fewer wound complications, shorter hospital stay, and earlier return of bowel function. [31][32][33][34][35] The overall cost reduction is also significant. 36 The role of laparoscopic resection in diverticulitis was initially controversial, given the inflammatory nature of the disease.…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
“…1 As laparoscopic surgery became more popular, studies demonstrated the safety and efficacy of laparoscopic colorectal surgery with the advantages of decreased pain, better cosmesis, fewer wound complications, shorter hospital stay, and earlier return of bowel function. [31][32][33][34][35] The overall cost reduction is also significant. 36 The role of laparoscopic resection in diverticulitis was initially controversial, given the inflammatory nature of the disease.…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
“…Despite some controversy in the early 1990s [1, 2], there is now more convincing evidence of the multiple potential benefits of a laparoscopic colectomy (LAC): smaller incision size leads to improved cosmesis; reduced postoperative pain; earlier return of gastrointestinal function, and earlier tolerance to diet [3]. These factors contribute to a faster recovery of the patient (compared to similar open operations) with a reduced utilization of hospital resources, reduced costs, and earlier return of the patient to normal activity [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Vale citar que apesar do grande número de publicações disponíveis, demonstrando, por exemplo, que as ressecções íleocólicas vídeo-assistidas são factíveis e seguras a factibilidade no tratamento da doença de Crohn, a maioria destas experiências não têm grupo controle ou consiste de ensaios não randomizados 19,20,21,22,23,24,25,26,27,28,29 .…”
Section: Resultados Da Videocirurgia Na Doença De Crohnunclassified